The Rib Metaphor in Hadith: A Study of Meaning and Gendered Social Relevance - Habiba, Siti; Raharusun, Agus suyadi; Kurmalasari, Tety; hanifah , Hanifah (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This article discusses and analyzes hadiths that address the creation of women. It is stated that women were created from a